Migrants with Irregular Status in Europe - Spencer, Sarah; Triantaphyllidu, Anna (2020)
This open access book explores the conceptual challenges posed by the presence of migrants with irregular immigration status in Europe and the evolving policy responses at European, national and municipal level. It addresses the conceptual and policy issues raised, post-entry, by this particular section of the migrant population. Drawing on evidence from different parts of Europe, the book takes the reader through philosophical and ethical dilemmas, legal and sociological analysis to questions of public policy and governance before addressing the concrete ways in which those questions are posed in current policy agendas from the international to the local level. As such this book is a valuable read to researchers, practitioners and policy makers as well as to students working on irregular migration in Europe in a comparative and/or country based perspective